The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.4103/1755-6783.95956
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and antimicrobial susceptibility pattern of clinical isolates of Enterococci at a tertiary care hospital in Mumbai, India

Abstract: Context:Enterococcus is considered an important nosocomial pathogen because of its intrinsic as well as acquired antibiotic resistance. It also has the potential of transferring vancomycin resistance to other organisms such as Listeria monocytogens and Staphylococcus aureus. Aims: The objective of the present study was to determine antibiotic-resistance pattern of Enterococcus with special reference to vancomycin. Settings and Design: A total of 54 clinical isolates of enterococci were collected during the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…Majority of Enterococcal infections were detected from hospitalized patients and more commonly seen among patients in intensive care units (ICUs) and surgical wards. Similar incidence rate were found by other authors [25]. Prolonged ICU hospital stay and increased invasive procedure applications are some possible explanations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Majority of Enterococcal infections were detected from hospitalized patients and more commonly seen among patients in intensive care units (ICUs) and surgical wards. Similar incidence rate were found by other authors [25]. Prolonged ICU hospital stay and increased invasive procedure applications are some possible explanations.…”
Section: Discussionsupporting
confidence: 87%
“…Present study revealed the most frequent infection was urinary tract infections (58.6%), followed by skin and soft tissue infections (31.6%) and blood stream infections (BSIs). Similar distribution of Enterococcal infections were reported in previous studies [22,24,25]. In these settings, enterococci are part of endogenous mixed flora commonly found in the gastrointestinal tract [26].…”
Section: Discussionsupporting
confidence: 84%
“…A similar rising trend of enterococcal resistance to various antibiotics was noted in another Indian study by Shinde et al in a tertiary care hospital in Mumbai. 24 Similar increasing resistance to quinolones and tetracycline group of drugs shown by Ali S et al 25 Study has revealed very encouraging results for nitrofurantoin and linezolid, as 94.9% and 97.81% of enterococcal isolates were susceptible to them respectively. Another antimicrobial which has given increasingly encouraging results is that all our isolates remained susceptible to fosfomycin (100%) and tigecycline (100%).…”
Section: Discussionmentioning
confidence: 55%
“…3,11,12 Maximum number of isolates was from urine which correlates with other studies. 3,12,13 38.2 % and 44.7 % of E. faecalis isolates were resistant to ampicillin and penicillin respectively in our study (Table-1) correlating with the study done by Shrihari et al 3 Amongst E. faecium isolates, 46.2 % were resistant to ampicillin and 53.8 % were resistant to penicillin (Table-2) correlating with study done by Golia et al 14 High level gentamicin resistance accounted to 22.4 % and 30.8 % for E. faecalis and E. faecium respectively by Kirby Bauer disc diffusion method (Table 1&2). Higher resistance to gentamicin leads to the failure of synergistic combination therapy with gentamicin and beta-lactam antibiotics/glycopeptides for serious infections.…”
Section: Discussionmentioning
confidence: 99%